Hyperhomocysteinemia and inflammatory biomarkers are associated with higher clinical SYNTAX score in patients with stable coronary artery disease - Djurić, Predrag; Mladenović, Zorica; Spasić, Marijan; Jović, Zoran; Marić-Kocijančić, Jelena; Prokić, Djordje; Subota, Vesna; Radojičić, Zoran; Djurić, Dragan (Vojnosanitetski pregled, 2021)
Background/Aim. Previous studies have confirmed a positive correlation between homocysteine levels and a greater risk for acute coronary syndrome and stroke, but there are no available data to support an association between homocysteine and inflammatory markers and the severity of coronary artery disease according to the clinical SYNTAX score in patients with stable angina. The aim was to determine the association between homocysteine and inflammatory biomarker levels: interleukin (IL)-6, high sensitive C-reactive protein (hs-CRP), fibrinogen, erythrocyte sedimentation rate (ESR) and the severity of coronary artery disease according to clinical SYNTAX score. Methods. Eighty-two patients with stable angina pectoris (average age 65 ± 8 years, 28.9% females) underwent coronary angiography and were divided into three groups according to the clinical SYNTAX score: the group I  < 22 (39 patients), the group II  23–32 (16 patients), the group III > 33 (27 patients). The severity and complexity of coronary artery disease were calculated by clinical SYNTAX score, multiplying the SYNTAX score with the modiﬁed ACEF score, based on the patients’ left ventricular ejection fraction, age and creatinine clearance (derived with Cockcroft–Gault equation). Results. Homocysteine levels were significantly higher in patients with high clinical SYNTAX score [the group I: median (interquartile range – IQR): 10.20 (3.97), the group II: 10.45 (5.77), the group III: 14.70 (7.50), p = 0.005]. Patients in the group III had significantly higher homocysteine levels compared to the group I (p = 0.001). We also found a positive association between inflammatory biomarkers (IL-6, hsCRP, fibrinogen, ESR) and the severity of coronary artery disease according to the clinical SYNTAX score (p = 0.017, 0.001, 0.032, 0.049 respectively). We detected significantly lower plasma levels of vitamin B12 in the group III and group II in comparison with the group I (the group I: median (IQR): 238 (160), the group II: 171 (160), the group III: 172 (102), p = 0.022), which indicates its important role in homocysteine metabolism. Conclusion. The elevated plasma levels of homocysteine, IL-6, hsCRP, fibrinogen, ESR were detected in patients with high clinical SYNTAX score (> 33). Our results showed that hyperhomocysteinemia and some inflammatory biomarkers can predict more severe and extensive coronary artery disease in stable angina patients.
Keywords: coronary disease; inflammation mediators; homocysteine; angina, stable